2019
DOI: 10.1186/s12885-019-6115-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between fecal enterotoxigenic B. fragilis with colorectal cancer

Abstract: Background: Enterotoxigenic Bacteroides fragilis (ETBF) is an enterotoxin-producing bacterium that possibily has a role in the occurrence and progression of colorectal cancer (CRC) by modulating the mucosal immune response and inducing epithelial cell changes. The aim of this study was to investigate the frequency of ETBF in stool samples of CRC patients and healthy volunteers. Methods: A total of 60 stool samples from confirmed CRC patients and 60 stool samples from healthy volunteers with no personal or fami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 22 publications
3
94
1
1
Order By: Relevance
“…With advances in sequencing techniques, studies have reported correlations between microbiota dysbiosis and CRC, and pathogenic microbiota that accelerate colon cancer progression have been identified [ 10 ]. For example, it has been reported that the enterotoxigenic Bacteroides fragilis contribute to colon carcinogenesis by producing toxins [ 11 ]. Together with numerous potential carcinogenic intestinal microorganisms, Fusobacterium nucleatum ( F. nucleatum ) has been reported to be a contributing factor to CRC progression based on its presence in CRC specimens [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…With advances in sequencing techniques, studies have reported correlations between microbiota dysbiosis and CRC, and pathogenic microbiota that accelerate colon cancer progression have been identified [ 10 ]. For example, it has been reported that the enterotoxigenic Bacteroides fragilis contribute to colon carcinogenesis by producing toxins [ 11 ]. Together with numerous potential carcinogenic intestinal microorganisms, Fusobacterium nucleatum ( F. nucleatum ) has been reported to be a contributing factor to CRC progression based on its presence in CRC specimens [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Boleij et al, 72.7% of early-stage colorectal tumors had a bft gene present, while 100% of late-stage tumors had a bft gene present [68]. This supports the role of enterotoxigenic Bacteroides fragilis in the progression of colorectal cancer, as late-stage tumors have more carcinogenic bacterial toxin Along with this, the abundance of enterotoxigenic Bacteroides fragilis in colorectal mucosa has been shown to be an independent predictor of three-year survival [69,71]. This supports the potential role of enterotoxic Bacteroides fragilis as both a driver and pathogenic passenger bacterium in colorectal carcinogenesis [34].…”
Section: Pathobionts and Colorectal Cancermentioning
confidence: 82%
“…Enterotoxigenic Bacteroides fragilis is a pathogenic bacterium that produces the enterotoxin Bacteroides fragilis toxin (bft) and is associated with colorectal cancer initiation and progression [68]. This occurs through modulation of the mucosal immune system and inducing alterations in epithelial cells, leading to a compromised colonic barrier [57,69]. Enterotoxic Bacteroides fragilis has been associated with colonic pre-neoplastic lesions and has been suggested to be a potential biomarker for early detection of colorectal carcinogenesis [70].…”
Section: Pathobionts and Colorectal Cancermentioning
confidence: 99%
“…The first study demonstrating an increased prevalence of ETBF in the stool specimens of CRC patients (38%) compared with the control group (12%) was conducted by Ulger Toprak and coworkers [ 95 ]. Different reports have shown an association between bft gene and CRC, particularly in the late stage (III/IV) of CRC [ 96 , 97 , 98 , 99 ] and significant associations of ETBF with tubular adenomas, serrated lesions, and low-grade dysplasia [ 100 ]. Interestingly, patchy bacterial biofilms composed predominately of E. coli and B. fragilis were identified in the colonic mucosa of patients with FAP, who develop benign precursor lesions (polyps) early in life.…”
Section: Bacterial Protein Toxins Causing Cell Signaling Alteratiomentioning
confidence: 99%